Adaptacja przedsiębiorstw do wymagań zrównoważonego rozwoju w świetle nowej ekonomii instytucjonalnej - Kudłak, Robert (Adaptation of enterprises to the requirements of sustainable development in the light of the new institutional economics, 2007)
The article seeks to explain the mechanism of adjustment of enterprises to the requirements of sustainable development. The analysis rests on the conceptions of the new institutional economics. This school of lhought invokes individual rationality of economic entities limited by the operation of institutions. Institutions are taken to be rules of behaviour following from the values, norms, and principles specific to the given socio-cultural environment. The new institutional economics differentiates between institutions and organisations. The latter (e.g. enterprises) result from the existence of institutions generating sets of rules which structure and intensify the processes of exchange. Changes of organisations are an effect of changes of institutions, both formal and informal. The adjustment of organisations is the resultant of three mechanisms: coercive, normative, and mimetic. Those mechanisms account for the way in which organisations alter in response to a change in their institutional environment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 516-525